DRAWING THE LAW STATE OF INDONESIA AFTER 75 YEARS OF INDEPENDENCE - Dadang Gandhi (Universitas Muhammadiyah Tangerang, 2020)
This study aims to determine and understand the extent to which the state administration of the unitary Republic of Indonesia is based on the 1945 Constitution of the Republic of Indonesia (UUDNRI 1945), which was established by the Preparatory Committee for Indonesian Independence on August 18, 1945, especially during the trip. As the rule of law by emphasizing the judicial power held by the Supreme Court, continued according to the 1949 Constitution of the Republic of Indonesia (RIS Constitution), then according to the Provisional Constitution of 1950 (UUDS 1950), according to the 1945 Constitution of the Presidential Decree on July 5, 1959, and according to the 1945 Constitution of the amendment and since the amendment has been completed up to now.